Transition to A True Currency: Impact of COVID-19 on The World Currency System - Indra Fajar Alamsyah; Juliana Juliana (Islamic Research, 2021)
The purpose of this paper is to manifest the unrefined design of the transition of the currency system from centralized fiat money based on the US Dollar to the real currency system that relies on the precious metals-based currency after reviewing the rapid changes from the COVID-19 phenomenon to various sectors of life, including the currency system. This paper used qualitative research with a historical analysis approach or historiography that deals with precious metals-based currency in the pastime, and it is used to produce relevant analyses for the future. First, states that prefer to transition to a precious metals-based currency ought to combine them in a single political institution that can provide a strong bargaining position in politics. Second, they have to withdraw gold reserves from the major central banks by making a trade balance surplus paid only in precious metals. Third, at this transitional stage, the use of oil reserves as a political economy of energy to withdraw gold reserves at the major central banks and the issuance of money is temporary until the state is fully stable and a new wave of gold reserves begin to enter. The underlying study will provide a comprehensive analysis of the currency system scheme in this modern era. Previous works have only focused on the superior aspects of the precious metals-based system and criticisms of the fiat money system, without detailing the steps to supersede the fiat money-based system. This paper used qualitative research with a historical analysis approach or historiography. It attempted to fill this glaring gap and expected to produce a study for implementation within the state scope.